دور التخطيط الاستراتيجي في تطوير مؤسسات التعليم العالي في الجمهورية العربية السورية ومعوقات تطبيقه"جامعة تشرين أنموذجاً" - شرف, سمير; عامر, وليد; عطيرة, عبير (Latakia University Journal - Economic and Legal Sciences Series, 2019)
هدف البحث إلى التعرف على ماهية التخطيط الاستراتيجي، وأهميته في تطوير التعليم العالي ومعوقات تطبيقه في جامعة تشرين من وجهة نظر العاملين الإداريين والعلميين فيها، و التعرف إلى الفروق في آراء عينة البحث في معوقات التخطيط الاستراتيجي في الجامعة تبعاً للمتغيرات(المؤهل العلمي، المرتبة العلمية، الخبرة). اشتملت عينة البحث على (80) عاملاً إدارياً وعلمياً للعام 2009- 2010. ولتحقيق هذا البحث صممت استبانة احتوت على (60) عبارة ووزعت إلى خمسة مجالات تتضمن المعوقات المتعلقة بـ (طبيعة التخطيط الاستراتيجي، إدارة الجامعة، الجامعة والعاملين فيها، الإدارة التعليمية العليا، البيئة المحيطة والمجتمع المحلي. أظهرت النتائج أن (21.47%) من أفراد العينة وافقوا على وجود المعوقات المذكورة في الإستبانة بدرجة مرتفعة جداً، و(32.93%) بدرجة مرتفعة، مقابل (26.18%) بدرجة متوسطة، في حين أن (14.56%) وافقوا على هذه المعوقات بدرجة منخفضة، و(5%) بدرجة منخفضة جداً. كما وجدت فروق دالة تبعاً للمؤهل العلمي، والمرتبة العلمية، وعدم وجود فروق دالة مرتفعة تبعاً لمتغير الخبرة. This research aims to explore the nature of strategic planning, its importance in developing higher education and the obstacles of its application at Tishreen University from the viewpoint of administrative and academic staff. It also aims to identify the differences in the beliefs of the research sample's population opinions about the impediments of strategic planning at university according to the variables (Education, qualification, Degree, and experience). The sample included 80 administrative staff members in the academic year 2009/2010. To achieve the object of the research, a questionnaire has included (60) items, distributed to five areas for barriers related with (nature of strategic planning, university administration, university and workers, the top teaching administration, surrounding environment and local community). The final results showed that (21.47%) of the examined sample approved of barriers with very high degree, and (%32.93) with high degree, and (%26.18) found that they agreeing with middle degree, also (5%) with little degree, and (%14.56) with very little degree. In fact, there are differences between qualification and education, but there are no high differences according to the years of experience.